INNOVATIVE PERSPECTIVE ON FORMATIVE ASSESSMENT; PERCEPTION AND EXPERIENCE OF EFL STUDENTS IN SIDOARJO - Al-Imamah, Hidayatul Ummah; Nurjati, Nunung; Rahayu, Endah Yulia; Irawan, Nico (Premise: Journal of English Education and Applied Linguistics, 2024)
In contemporary secondary EFL (English as a Foreign Language) education, formative assessments play a critical role in enhancing students' language proficiency. This research explores the perceptions and experiences of EFL students in Sidoarjo regarding formative assessment practices. The central research question focuses on how students' perceptions and experiences with formative assessments influence their engagement and language development. Employing a phenomenological approach, qualitative data were collected through in-depth interviews and classroom observations with 25 secondary EFL students. Thematic analysis identified recurring patterns and themes, providing a comprehensive understanding of how these students perceive and experience formative assessment practices. Findings reveal that students perceive their experiences with interactive tools like Kahoot! and Quizizz as highly engaging and motivating, which they believe contributes to a more dynamic and participatory learning environment. Additionally, students' experiences with timely and constructive feedback were pivotal in helping them recognize and correct mistakes, thereby improving their language skills. Peer assessment and self-reflection were also seen as fostering a more student-centered learning environment, though some students encountered challenges in consistently understanding and applying these methods. These challenges underscore the need for better support and resources to ensure effective implementation. The research concludes that well-designed formative assessments, when aligned with students' perceptions and experiences, can substantially improve engagement and language proficiency. Recommendations include integrating interactive tools, emphasizing constructive feedback, and promoting peer assessment and self-reflection. Future research should explore the long-term impacts of formative assessments on EFL learning outcomes. This study underscores the transformative potential of formative assessments in EFL education and advocates for continuous support to enhance their effective implementation.